2010
DOI: 10.1002/j.2161-1939.2010.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Wellness and Age, Matriculation, and Relationship Status of Counselor Education Doctoral Students

Abstract: The authors examined the extent of the relationship between wellness and age, number of years spent in a counselor education and supervision doctoral program that was accredited by the Council for Accreditation of Counseling and Related Educational Programs (2009), and student relationship status. Insight into wellness of this population and implications for counselor educators and students are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…While previous research provides support to the importance of wellness, thus far, few empirical studies examined implementation of wellness practices in counselor education programs (Perepiczka & Balkin, 2010; Roach & Young, 2007). Roach and Young (2007) conducted a study with 204 counselor trainees to investigate the effect of counselor education programs on trainee’s wellness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While previous research provides support to the importance of wellness, thus far, few empirical studies examined implementation of wellness practices in counselor education programs (Perepiczka & Balkin, 2010; Roach & Young, 2007). Roach and Young (2007) conducted a study with 204 counselor trainees to investigate the effect of counselor education programs on trainee’s wellness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the past decade, wellness in counselor education programs has begun to gain traction (Hartwig Moorhead, Gill, Barrio Minton, & Myers, 2012;Lenz, Sangganjanavanich, Balkin, Oliver, & Smith, 2012;Myers, Mobley, & Booth, 2003;Perepiczka & Balkin, 2010;Roach & Young, 2007;Smith, Robinson, & Young, 2007). The Council for the Accreditation of Counseling and Related Educational Programs [CACREP] has voiced the need for wellness, well-being, and self-care to be representative standards within counselor training and, in the 2016 CACREP standards, core learning standards present rigorous expectations for all counselors-in-training to deepen their understanding of wellness practices and self-care strategies needed within the counseling profession.…”
Section: Wellness In Counselor Trainingmentioning
confidence: 99%
“…Researchers of several quantitative studies have recommended using qualitative approaches in future research (see Lawson, 2007; Lenz et al, 2012; McDonald, 2011; Perepiczka & Balkin, 2010; Wester, Trepal, & Myers, 2009). Specifically, authors (i.e., Lenz et al, 2012; Perepiczka & Balkin, 2010; Wester et al, 2009) have suggested that qualitative research would give a more in‐depth understanding of wellness, allowing participants to speak to the factors that affect individual wellness. A further limitation of previous research is that samples were typically convenience or purposive and were collected from a single university in one geographic location of the United States.…”
mentioning
confidence: 99%
“…Research focused exclusively on the wellness of doctoral-level counselor trainees is limited (see Perepiczka & Balkin, 2010;Pierce & Herlihy, 2013). Pierce and Herlihy (2013) stated that a sacrifice of some areas of wellness was a common occurrence for counselor education doctoral students and that more faculty and collegial support could be beneficial for promoting wellness.…”
mentioning
confidence: 99%
See 1 more Smart Citation